The greek version of the professional quality of life (ProQoL) scale version 5. (14th October 2021) - Lakatamitou, I; Middleton, N; Paikousis, L; Kouta, C; Lambrinou, E
Abstract: Background: The Professional Quality of Life (ProQoL) scale is one of the most widely measures of compassion satisfaction and fatigue used, despite there is not much of published evidence to support its validity. The ProQoL scale assesses multiple domains of work experiences; compassion satisfaction, burnout and secondary traumatic stress. Our aim was to examine the psychometric properties of the Greek version of the ProQoL scale version 5 (Gr-ProQoL-5). Method: A methodological study was contacted in order to assess the construct validity and reliability of the Gr-ProQoL-5. For that reason, 264 questionnaires were administrated by Greek-Cypriot healthcare professionals (HPs). Confirmatory factor analysis (CFA) and Exploratory factor analysis (EFA) were conducted to examine the relationship between the three Gr-ProQoL-5 dimensions (compassion satisfaction, burnout and secondary traumatic stress). Cronbach's a was calculated as well. Results: CFA for Gr-ProQOL-5, did not confirm the initial scale's dimensions. In EFA five models were emerged. The models were then tested with CFA and after a panel discussion, the research team decided to keep one final model for the Gr-ProQoL-5. Items 1, 2, 4, 10, 15, 17 and 29 were eliminated from the analysis due to low communalities and multiple components loading. Three components were found representing compassion satisfaction, burnout and secondary traumatic stress. Conclusions: The Gr-ProQoL-5 is an adequate instrument to assess ProQoL in Greek-Cypriot HPs and may be valuable for designing effective interventions to reduce burnout and compassion fatigue, and promote compassion satisfaction of HPs. More than ever and in the era of the pandemic the ProQoL seems to be a necessary quality indicator for health care systems. FUNDunding Acknowledgement: Type of funding sources: None.